Poverty Reduction and Growth Trust-Guidance Note on New Enhanced Safeguards for Debt Sustainability and Capacity to Repay. - International Monetary Fund. Strategy, Policy, and Review Department (Washington, D.C. : International Monetary Fund, 2022)
Poverty Reduction and Growth Trust-Guidance Note on New Enhanced Safeguards for Debt Sustainability and Capacity to Repay.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Lending and Debt Problems; Monetary Policy; Political Economy